A case study : 2D Vs 3D parallel differential equation toward tumor cell detection on multi-core parallel computing atmosphere - Islam, Md. Rajibul; Alias, Norma (UCSI Publishing House, 2010)
This study thrashes out some of the visualisation and computational challenges encountered in the field of neuroscience. With the intention to address such computational challenges; we recognised the particular significance of the iterative solvers and parallel algorithms on Multi-Core parallel computing atmosphere. In order to detect tumour cells, 2D and 3D Partial Differential Equations (PDE) are considered and compared by using Multi-Core parallel computing atmosphere with visualisation, communication and data analysis. The performance analysis of Multi-Core computing is presented in provisions of speedup, efficiency, effectiveness and temporal performance where the use of 2D and 3D PDEs and parallel algorithms was found to give in remarkable results.